2014
DOI: 10.1002/ppap.201400099
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Particle Mass and Flow Rate on Plasma Polymerized Allylamine Coated Quartz Particles for Humic Acid Removal

Abstract: Plasma polymerized allylamine films were deposited onto quartz particles for the removal of humic acid, a common water contaminant. Allylamine flow rates of 6.6 and 11.5 standard cubic centrimetres per minute (sccm) were used and the mass of particles varied from 50 to 500 g. At an allylamine flow rate of 6.6 sccm, the atomic concentration of carbon and nitrogen decreased with increasing mass of particles. The isoelectric point and number of positively charged amine groups increased as the allylamine flow rate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2019
2019

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 54 publications
0
5
0
Order By: Relevance
“…Little humic acid is removed at plasma powers of 4–10 W while powers of 15–40 W increased the mass of humic acid removed to between 0.007 and 0.016 mg g −1 . The highest humic acid removed of approximately 0.023 mg g −1 was observed at the highest plasma powers of 50 and 60 W. Our previous research has indicated that a ppAA film deposited onto quartz particles at a power of 60 W, a flow rate of 6.5 sscm, and a deposition time of 60 min had a PZC of 7.4 and 2.24 positively charged groups per nm 2 . Although the PZC of ppAA surface deposited at 60 W with polymerization times less than 60 min, as featured in Section 3.1, is not known.…”
Section: Resultsmentioning
confidence: 90%
See 2 more Smart Citations
“…Little humic acid is removed at plasma powers of 4–10 W while powers of 15–40 W increased the mass of humic acid removed to between 0.007 and 0.016 mg g −1 . The highest humic acid removed of approximately 0.023 mg g −1 was observed at the highest plasma powers of 50 and 60 W. Our previous research has indicated that a ppAA film deposited onto quartz particles at a power of 60 W, a flow rate of 6.5 sscm, and a deposition time of 60 min had a PZC of 7.4 and 2.24 positively charged groups per nm 2 . Although the PZC of ppAA surface deposited at 60 W with polymerization times less than 60 min, as featured in Section 3.1, is not known.…”
Section: Resultsmentioning
confidence: 90%
“…Little humic acid is À1 was observed at the highest plasma powers of 50 and 60 W. Our previous research has indicated that a ppAA film deposited onto quartz particles at a power of 60 W, a flow rate of 6.5 sscm, and a deposition time of 60 min had a PZC of 7.4 and 2.24 positively charged groups per nm 2 . [27] Although the PZC of ppAA surface deposited at 60 W with polymerization times less than 60 min, as featured in Section 3.1, is not known. Our previous work has, however, shown that the PZC decreases as the number of positively charged groups per nm 2 decreases.…”
Section: Influence Of Plasma Power On Surface Chemistry and Humic Acimentioning
confidence: 99%
See 1 more Smart Citation
“…It is a relatively simple, rapid, dry, and environment-friendly technique that is used to modify the surface of a great variety of materials. Even if this technique is normally used to modify the surface of different polymeric substrates, it has been used with success to modify different nanoparticles and other surfaces like zinc oxide, iron oxide, aluminum oxide, titanium oxide, carbon nanofibers (CNFs), CNTs, nanoclays [5,7,15,16,[31][32][33][34][35][36], and quartz [37,38]. Treatment with plasma can add a nanometric film that covers nanoparticles, modifying their surface properties.…”
Section: Introductionmentioning
confidence: 99%
“…If the plasma modification is carried out by using a monomer (plasma polymerization), this can generate a polymeric coating like the specific polymeric matrix over the nanoparticle with a desired increase in surface interaction, promoting an improvement in the adhesion between phases and the transference of properties between them [15,16]. For example, Jarvis and Majewski [37,38] have recently investigated changing the surface of quartz particles from hydrophobic to a hydrophilic character by using plasma treatment of allylamine. Longer polymerization times increased the number of positively charged groups and their hydrophilic behavior.…”
Section: Introductionmentioning
confidence: 99%